Efficiency of Ipratropium Bromide and Albuterol Deposition in the Lung Delivered via a Soft Mist Inhaler or Chlorofluorocarbon Metered‐Dose Inhaler. Issue 2 (6th March 2016) - MacGregor, TR; ZuWallack, R; Rubano, V; Castles, MA; Dewberry, H; Ghafouri, M; Wood, CC
Abstract : The propellant‐free Combivent Respimat Soft Mist Inhaler (CVT‐R) was developed to replace the chlorofluorocarbon‐propelled Combivent metered‐dose inhaler (CVT‐MDI). This steady‐state pharmacokinetic (PK) substudy evaluated drug lung‐delivery efficiency, using data from two phase III safety and efficacy trials. PK parameters were obtained from well‐controlled population PK analyses. Area under the plasma concentration–time curve (AUC), maximum observed plasma concentration (Cmax ), and minimum observed plasma concentration (Cmin ) showed systemic exposure to ipratropium bromide and albuterol delivered via the CVT‐R was proportional to ex‐mouthpiece delivered dose. Although the labeled dose of ipratropium bromide in the CVT‐R was half that in the CVT‐MDI, the systemic exposure was comparable. No PK interaction for the ipratropium bromide and albuterol Respimat drug components was demonstrated. Ipratropium bromide alone resulted in similar exposure to the combination of ipratropium bromide and albuterol. These results show that CVT‐R delivers drug more efficiently to the lung than CVT‐MDI.